The Novel Oral Drug Subetta Exerts an Antidiabetic Effect in the Diabetic Goto-Kakizaki Rat: Comparison with Rosiglitazone. (8th May 2013) - Bailbé, Danielle; Philippe, Erwann; Gorbunov, Evgeniy; Tarasov, Sergey; Epstein, Oleg; Portha, Bernard
Abstract : The aim of the present study was to evaluate the potential antidiabetic effects of two-component drug Subetta and its components (release-active dilutions of antibodies to β -subunit insulin receptor (RAD of Abs to β -InsR) and to endothelial nitric oxide synthase (RAD of Abs to eNOS)) in Goto-Kakizaki (Paris colony) (GK/Par) diabetic rats. Subetta was administered orally for 28 days once daily (5 mL/kg) and compared to its two components (2.5 mL/kg), Rosiglitazone (5 mg/kg), and vehicle (5 mL water/kg). At day 28, fasting plasma glucose levels were significantly decreased only in Subetta and Rosiglitazone groups as compared to vehicle (P < 0.01 ): 147 ± 4 mg/dL and 145 ± 4 mg/dL and 165 ± 4 mg/dL, respectively. The data of glucose tolerance test showed that Subetta and RAD of Abs to β -InsR (similar to Rosiglitazone) prevented significantly (P < 0.01 ) the age-related spontaneous deterioration of glucose tolerance as seen in the control group. Subetta and RAD of Abs to β -InsR did not significantly modify the glucose-induced insulin secretion. Chronic administration of Subetta and RAD of Abs to β -InsR improves glucose control, to an extent similar to that of Rosiglitazone. We hypothesize that Subetta and RAD of Abs to β -InsR mostly act via an insulin-sensitizing effect upon target tissues.